Visitor’s satisfaction towards activities provided at Keda Resort Bendang Man, Sik Kedah - Mohamad Sabri, Nursabrina (2019)
Visitor’s satisfaction towards the activities provided is important for the management in order to satisfy visitors in KEDA Resort Bendang Man, Sik. This study is conducted to measure the respondent’s reason visited to enjoy various of activities organized in KEDA Resort Bendang Man, Sik and to identify the factors affecting visitor’s satisfaction level towards a range of factors such as facilities and services provided in the area. The data was collected by using a questionnaire in this study. The findings showed that the highest visitor’s reason was to be with members and group while visiting KEDA Resort Bendang Man, Sik with the mean, M=4.50. Then, there were five factors affecting visitors’ satisfaction level such as activities, accommodation, safety, facilities and price. In this study, accommodation factor showed the highest total mean of satisfaction (M=3.50) which is visitors were most satisfied with dorm or hostel provided in KEDA Resort Bendang Man, Sik. This study also identified whether there are any differences in terms of satisfaction based on socio demographic with five factors. The findings showed that there was a significant different in relation to satisfaction on accommodation and gender (p=0.01) and also on facilities with value was p=0.01. The result shows that both gender is satisfied with accommodation and facilities in the area. In addition, this study also found that visitors with higher income are more satisfied with activities provided with value was M=3.85 compared to lower income visitors. In general, visitors are satisfied with all activities but the management need to consider with the small issues such as cleanliness, maintenance, landscaping and others whether to attract more visitors to visit this resort for future.